WINNER/LOSER STOCK, FINANCIAL RISK, CASH HOLDING, DAN TAX PLANNING: PENGARUHNYA TERHADAP INCOME SMOOTHING DALAM PERUSAHAAN - Herawati, Rosa Afri; Mansur, Fitrini; Ridwan, Muhammad (Jurnal Bina Akuntansi, 2025)
Profit plays a pivotal role in the analysis of financial statements, reflecting an organization's capacity to effectively manage resources while shaping market perceptions regarding its financial stability and potential for future growth. The practice of income smoothing often emerges from conflicts of interest and asymmetrical information, allowing management to manipulate reported profits for personal or corporate gain, thereby presenting a façade of stability in earnings over time. This research aims to prove and test empirically how winner/loser stocks, financial risk, cash holding, and tax planning strategies on income smoothing within the property and real estate industries. Utilizing a quantitative methodology, secondary data was obtained from the annual and sustainability reports of firms listed on the Indonesia Stock Exchange for the years 2021 to 2023. A purposive sampling method was employed to select a sample of 31 companies, with data spanning three years. The data was analyzed through logistic regression using SPSS 29. The findings reveal that the independent variables, when considered collectively, have a significant impact on income smoothing practices. Specifically, winner/loser stocks negatively affects income smoothing, while cash holding positively influences it. On the other hand, financial risk and tax planning do not exhibit any substantial impact.